Correlation Between the Ratio of Uric Acid to High-Density Lipoprotein Cholesterol (UHR) and Diabetic Retinopathy in Patients with Type 2 Diabetes Mellitus:A Cross-Sectional Study - Wang L; Liu L; Luo H; Wu Y; Zhu L (Diabetes, Metabolic Syndrome and Obesity)
Leran Wang,1 Lei Liu,2 Huilan Luo,3– 5 Yiling Wu,3– 5 Lingyan Zhu3– 5 1Queen Mary School, Jiangxi Medical College, Nanchang University, Nanchang City, People’s Republic of China; 2Department of Endocrinology, Lu’an Hospital of Anhui Medical University, Lu’an City, Anhui Province, People’s Republic of China; 3Department of Endocrinology and Metabolism, the First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang City, People’s Republic of China; 4Jiangxi Clinical Research Center for Endocrine and Metabolic Disease, the First Affiliated Hospital of Nanchang University, Nanchang City, People’s Republic of China; 5Jiangxi Branch of National Clinical Research Center for Metabolic Disease, Nanchang City, People’s Republic of ChinaCorrespondence: Lingyan Zhu, Jiangxi Branch of National Clinical Research Center for Metabolic Disease, No. 17, Yongwaizheng Street, Nanchang City, Jiangxi Province, People’s Republic of China, Tel +86-13870690788, Email zly982387@126.comBackground/Objective: Considering the uncertain relationship between high-density lipoprotein cholesterol (HDL-C) and uric acid (UA) with diabetic retinopathy (DR),this study investigates the link between Uric Acid to High-Density Lipoprotein Cholesterol (UHR) and DR in T2DM patients, evaluating its potential for DR diagnosis and early prediction.Study Design and Data Collection: This retrospective study analyzed 1450 type 2 diabetes patients, divided into NDR and DR groups by retinal exams. We gathered demographic and clinical data, calculated UHR, and explored its correlation with DR development.Outcomes: Individuals diagnosed with diabetic retinopathy (DR) exhibited a markedly elevated uric acid to high-density lipoprotein cholesterol (UHR) ratio when contrasted with those without DR (NDR), achieving statistical significance with a P-value below 0.001. The Mantel-Haenszel chi-square test for linear association validated a pronounced positive correlation between the UHR ratio and the incidence of DR (P< 0.001). Binary logistic regression analysis revealed that age, glycated hemoglobin (HbA1c), uric acid (UA), high-density lipoprotein cholesterol (HDL-C), and the UHR ratio were all independent risk factors for the development of DR in patients with type 2 diabetes. Furthermore, the receiver operating characteristic (ROC) curve analysis indicated that the UHR ratio was the most precise predictor for diagnosing DR, with an area under the ROC curve (AUC) of 78.4%, a sensitivity of 87%, and a specificity of 60.6%.Conclusion: Our research has found that the UHR ratio is an independent risk factor for diabetic retinopathy (DR) in patients with type 2 diabetes and can serve as a readily available indicator that takes into account both metabolic status and inflammatory status for the early detection of DR.Keywords: uric acid to high-density lipoprotein cholesterol ratio, UHR, Type 2 diabetes mellitus, diabetic retinopathy